Effect of Different Stern Flap Position and Size as an Energy Saving Device (ESD) for Increasing Fishing Boat Speed. Issue 1 (June 2020) - Klara, S; Mahmuddin, F; Hariyanto, S; Sitepu, G; Aman, A A
Abstract: One of the most issues on a boat for using energy is resistance. Therefore some energy is needed to be able to overcome the boat resistance. The total resistance depends on the speed of the boat. By reducing the resistance, it will affect the energy usage on the boat. One way to reduce the boat resistance is by installing a stern flap to the stern. Stern flap is a new addition on the stern appendage. Previous studies, the stern flap was able to reduce the resistance. The reduction of resistance occurred on boats can reduce fuel consumption, so it can be one of the innovations in combating the energy crisis. This study used an experimental method that analyzes the position and size of the stern flap, where each position and size of the flap were tested at the same load. From the results and analysis, it shows that the changing position of the stern flap on the surface of the water will increase the boat speed by 4.62% and the changing size of the stern flap size to 85 × 80 cm will increase the speed of the boat by 3.82%.